2020
DOI: 10.14295/bds.2020.v23i2.2287
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Awareness, and Practice of Dentists in Preventing- Novel Corona Virus (COVID-19) Transmission - A Questionnaire Based Cross-Sectional Survey.

Abstract: Background: The global issue that urges the public health emergency is the outbreak of the Novel Corona Virus strain (COVID-19). Dentists being are highly prone to airborne transmission during dental treatment due to aerosols generated by various dental procedures on patients with COVID-19. Taking this fact into consideration, the present survey research was mainly aimed at evaluating the knowledge, attitude, and practice of dentists in preventing the disease transmission of Novel Coronavirus (COVID-19). Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 15 publications
(19 reference statements)
2
17
0
Order By: Relevance
“…The highly contagious nature of the COVID-19 might have led the dentists to be skeptical for each dental procedure as an aerosol-generating procedure. A similar nding was observed by Teja et al, 13 where they reported that 60% of the participants felt that restorative procedures and any procedures producing aerosols have higher chances to transmit COVID-19 and 35% of them felt that surgical procedures have higher chances of the transmission of infection. 13 A total of 230 (60%) respondents were practicing only emergency dental services during the pandemic which is in accordance with CDC guidelines which states that non-emergency dental procedures should…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The highly contagious nature of the COVID-19 might have led the dentists to be skeptical for each dental procedure as an aerosol-generating procedure. A similar nding was observed by Teja et al, 13 where they reported that 60% of the participants felt that restorative procedures and any procedures producing aerosols have higher chances to transmit COVID-19 and 35% of them felt that surgical procedures have higher chances of the transmission of infection. 13 A total of 230 (60%) respondents were practicing only emergency dental services during the pandemic which is in accordance with CDC guidelines which states that non-emergency dental procedures should…”
Section: Discussionsupporting
confidence: 82%
“…The self-reported online questionnaire was developed by the authors after reviewing the pertinent literature. [11][12][13] The questions were prepared to emphasize the awareness related to the aerosol and ventilation system in their practice. Suggestions for improvement in the questionnaires were incorporated from subject experts and modi ed accordingly.…”
Section: Methodsmentioning
confidence: 99%
“…Similar responses were reported in a few previous studies. 15 , 16 Although various drugs for COVID-19 are being tested, none have been approved as first-line treatment. Hence, the current treatment modality is supportive rather than imperative.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have reported a consensus of proper PPE usage among dentists. 14 , 15 As per the CDC guidelines on infection control protocols, universal precautions should be taken at all times irrespective of the pandemic or epidemic status. The highly contagious nature of COVID-19 warrants proper infection control protocols.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation